Regulating the distribution of State advertising to private news media organizations: a cross-country comparative analysis - Mutu, Adriana; Martori-Muntsant, Aida (Derecom. Revista Internacional de Derecho de la Comunicación y de las Nuevas Tecnologías, 2023)
In this paper we examine the institutional mechanisms, legislative and regulatory procedures for the allocation of State advertising to private news media organizations in France, Germany and the United Kingdom. Based on an extensive literature review, this research aims to fill in the gaps in prior research by applying a qualitative framework developed using indicators derived from scholarly work on political science and political communication. The parameters selected for analysis come from prior interdisciplinary research and focus on the legal and regulatory frameworks, competent authorities involved in the process of tender preparation and awarding of advertising contracts, monitoring and transparency mechanisms. The central research issue is: what are the rules, laws or regulations governing public spending on State advertising in the countries chosen? Data were collected from multiple publicly available national sources, including central government information and ministerial data, national and regional media regulatory authorities, as well as reports published by various stakeholders. Results show cross-country variations. This work adds to current research as it provides an in-depth analysis of the French, German and British cases, enhancing our understanding of the available frameworks for regulating State advertising. Secondly, it maps out institutional and media governance arrangements, complementing previous research on media governance across different European countries.